Quality analysis of patient information on surgical treatment of haemorrhoids on the internet. - Yeung, T; D'Souza, N (2013)
INTRODUCTION: Haemorrhoids are the most common benign condition seen by colorectal surgeons. At clinic appointments, advice given about lifestyle modification or surgical interventions may not be understood fully by patients. Patients may use the internet for further research into their condition. However, the quality of such information has not been investigated before. This study assessed the quality of patient information on surgical treatment of haemorrhoids on the internet. METHODS: Four searches were carried out using the search terms 'surgery for haemorrhoids' and 'surgery for piles' on two search engines (Google and Yahoo). The first 50 results for each search were assessed. Sites were evaluated using the DISCERN instrument. RESULTS: In total, 200 websites were assessed, of which 144 fulfilled the inclusion criteria. Of these, 63 (44%) were sponsored by herbal remedies for haemorrhoids. Eighty-nine (62%) mentioned conservative treatment options but eleven (8%) did not include surgery in their treatment options. Only 38 sites (27%) mentioned recurrence of haemorrhoids following surgery and 28 sites (20%) did not list any complications. Overall, 19 websites (14%) were judged as being of high quality, 66 (45%) as moderate quality and 58 (40%) as low quality. CONCLUSIONS: The quality of information on the internet is highly variable and a significant proportion of websites assessed are poor. The majority of websites are sponsored by private companies selling alternative treatments for haemorrhoids. Clinicians should be prepared to advise their patients which websites can provide high-quality information on the surgical treatment of haemorrhoids.